Covalent self-assembly in two dimensions: connecting covalent organic framework nanospheres into crystalline and porous thin films - Sasmal, Himadri Sekhar; Halder, Arjun; Kunjattu, Shebeeb; Dey, Kaushik; Nadol, Athulya; Ajithkumar, Thalasseril G.; Bedadur, Prachiti Ravindra; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Insolubility of covalent organic frameworks (COFs) in organic solvents is one of the major obstacles for the potential application of these extended networks such as drug delivery, sensing, optoelectronics, and semiconductor device fabrication. The present work proposes a unique way to make uniform, solution-processable, crystalline, and porous COF nanospheres directly from the homogeneous solution of amine and aldehyde via spatial and temporal control of the nucleation and growth. This strategy of direct nucleation simultaneously showcases the caliber to tune the size of the COF nanospheres from 25 to 570 nm. We have also demonstrated the concept of mesoscale covalent self-assembly of those solution-processable COF nanospheres in the liquid-liquid interface (DCM-water bilayer) for the very first time, transmuting them into self-standing COF thin films with long-range ordered arrangements in two dimensions. The crystalline and porous (with TpAzo showing highest S-BET of 1932 m(2) g(-1)) free-standing COF thin films could be fabricated in a wide range of thicknesses from as low as 21 nm to as high as 630 nm. Both beta-ketoenamine (TpAzo, TpDPP) and imine (TpOMeAzo, TpOMeDPP) linked COF thin films have been synthesized via mesoscale covalent self-assembly of the solution-processable COF nanospheres illustrating the generality of this eloquent methodology. Further, the solution processability has been tested and utilized to cast COF thin films uniformly in the inner and outer surface of an alumina hollow fiber membrane. The COF thin film-alumina hollow fiber membrane composites have showcased promising selective molecular separation of He and O-2, He and CO2, and He and N-2.